Intermittent fasting: a strategy to counteract aging linked to oxidative stress - Hidalgo-Silva , Diana; López-Noguerola , José Sócrates; Sánchez-Gutiérrez , Manuel; Madrigal-Santillán , Eduardo Osiris; Izquierdo-Vega, Jeannett Alejandra (Mexican Journal of Medical Research ICSA, 2022)
Aging is a multifactorial deterioration process that occurs in the life of an organism, which seems to be linked to oxidative stress. Intermittent fasting (IF) consists of food restriction with intermediate periods of regular food intake repeatedly. Various studies in human beings and experimental animal models have shown that intermittent fasting counteracts various alterations associated with age and weight loss, a decrease in the concentration of insulin, glucose, and serum lipids, and oxidative stress, improving antioxidant defense. This review summarizes the evidence available to date in PubMed to analyze the effects of IF on the aging process and its link with oxidative stress. The results suggested that food restriction on alternate days and with a time restriction improves aging processes by decreasing oxidative stress markers and increasing autophagy related to longevity. IF represents a promising non-pharmacological alternative to improve health in the adult population. However, more studies are required to know the chronic effect of fasting and recognize its effects as a therapy in diseases associated with aging.